1991
DOI: 10.1007/bf00024766
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in aquatic macrophytes drifting in a large river

Abstract: Macrophytes drifting throughout the water column in the Detroit River were collected monthly from May to October 1985 to estimate the quantities of heavy metals being transported to Lake Erie by the plants .Most macrophytes (80-92% by weight) drifted at the water surface . Live submersed macrophytes made up the bulk of each sample . The most widely distributed submersed macrophyte in the river, American wildcelery (Yallisneria americana), occurred most frequently in the drift . A total of 151 tonnes (ash-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Such a synergism promoting the photoreduction of Hg(II) simultaneously is in line with the large differences observed between day and night emission of Hg(0) in the field . More generally, both IHg and MeHg in macrophytes might be dispersed by drifting or hydrochory as well as through herbivory .…”
Section: Release Of Hg From Macrophytessupporting
confidence: 70%
“…Such a synergism promoting the photoreduction of Hg(II) simultaneously is in line with the large differences observed between day and night emission of Hg(0) in the field . More generally, both IHg and MeHg in macrophytes might be dispersed by drifting or hydrochory as well as through herbivory .…”
Section: Release Of Hg From Macrophytessupporting
confidence: 70%
“…Their decay may release chemicals back to the water and/or to the sediments. It has further been found that drifting macrophytes can act as a vehicle for chemical transport in rivers (2).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the numerous surface buoys marking our gear in these areas, we received complaints about these obstacles interfering with angling and boating and frequently lost gear due to boats accidentally running them over, or tampering by disgruntled anglers and boaters who would cut buoy lines or remove the gear completely. In addition, uprooted mats of submersed aquatic macrophytes (Manny et al., 1991), tree branches, and other items regularly float downstream and tend to catch on the float line. When enough of this material accumulated on the gear during the time period between inspections (typically 1 week), it created enough weight and drag to pull the floats underwater.…”
Section: Introductionmentioning
confidence: 99%